The Role of School Principals in Growing Teacher Literacy Practice at SMP Muhammadiyah 12 GKB Gresik - Arif, Ichwan (Proceeding International Conference on Lesson Study, 2023)
Literacy character, especially writing, is very important for teachers to have in their competence. This character will increase and develop when the school principal has a vision, mission and commitment to improving it. One of them is Sustainable Professional Development (PKB), which is the school’s flagship program. Through this role, the principal can provide motivation, enthusiasm and appreciation to teachers in improving scientific competence in the field of writing. From this background, the research objectives of this paper are (1) to find out how the principal of Muhammadiyah 12 Middle School (Spemdalas) GKB Gresik develops teachers’ literacy skills and (2) to find out the role of the principal of Muhammadiyah 12 Middle School (Spemdalas) GKB Gresik in developing teacher literacy abilities. The method used in this paper is a quantitative research method. This method is to explore or photograph social situations that will be researched thoroughly, broadly and in depth. The aim is to systematically describe the facts or characteristics of a particular population or a particular field in a factual and accurate manner. IHT is a model and strategy for school principals in providing enlightenment in improving writing skills through internal training carried out by the school. External training as schools send teachers to take part in training held by agencies outside the school. Gathering is a medium for appreciating school principals when writers achieve proud achievements. The results of this research, the principal of Muhammadiyah 12 Middle School GKB Gresik used IHT strategies, external training and gatherings to develop teachers’ literacy character. With these 3 strategic steps, teachers at SMP Muhammadiyah 12 GKB Gresik have the opportunity and motivation to improve their scientific competence, especially in terms of literacy characteristics in writing opinions and news about school and student activities.